THE SIDE EFFECTS OF CHEMOTHERAPY IN GLIOMA - Raisa, Neila; Marhaendraputro, Eko Arisetijono (Malang Neurology Journal, 2019)
The increasing number of people who survive in the long term because of the advanced of glioma therapy with chemotherapy causes more slowly emerging neurologic side effects. Currently, there were three medical treatments are approved by the FDA for the management of glioblastoma namely temozolomide, carmustine wafer, and bevacizumab. However, most of the traditional chemotherapy drugs have a target in cell proliferation and cause toxicity of healthy cells. The side effects of chemotherapy on central nervous systems are chemobrain, acute encephalopathy, leukoencephalopathy, cerebellar dysfunction, and spinal cord toxicity. In addition, severe chemotherapy side effects may also occur in the peripheral nervous system called Chemotherapyinduced peripheral neuropathic pain (CIPNP). The clinician should recognize the symptoms of those side effect in glioma patients who received chemotherapy.